PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK TEMA 7 SUBTEMA 2 INDAHNYA KERAGAMAN BUDAYA NEGERIKU PEMBELAJARAN 1 - Fena Diazayu Safitri; Wawan Syahiril Anwar, Santa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on the results of the research analysis that has been carried out, it shows that the product produced from the development of this Flipbook-Based E-module is stated to be very feasible and able to attract students' attention which has an impact on the assessment of cognitive abilities. This is evidenced by the results of media validation obtaining a percentage of 94.28%, language experts obtaining a percentage of 90%, material experts obtaining 88%, the development of flipbook- based e-modules on theme 7 sub-theme 2 the beauty of my country's cultural diversity learning 1 obtained the category "very feasible" overall the percentage obtained was 91% and the results of the student response questionnaire obtained a percentage of 97.41%. So it can be concluded that the development of flipbook- based e-modules on theme 7 sub-theme 2 the beauty of my country's cultural diversity learning 1 is "very feasible" to be applied in learning at SDN Cilangkap 8, Depok City.